BEKSAN TRUNAJAYA IN THE CONTEXT OF CULTURAL RELATIONS AND POWER OF KERATON YOGYAKARTA IN HABITUS PIERRE FELIX BOURDIEU PERSPECTIVE - Dina Arumsari, Mela; Kuswarsantyo, Kuswarsantyo; Susanto, Moh. Rusnoto (Yayasan Education and Social Center, 2024)
Sri Sultan Hamengku Buwana, I historically created Beksan Trunajaya as a ballet performance for the Trunajaya team, which was part of the Nyutra troops (soldiers). This Beksan is based on the name of the Tarunajaya courtier group (Taruna means young, and jaya means winning), by the nature of the dance that uses lawung weapons (a kind of spear), which suggests war training. Sultan Hamengku Buwana, I took the name Beksan Trunajaya to instill a heroic spirit through ideals to continue Sultan Agung's struggle to defend his homeland against the Dutch. Research objectives: (1) to describe the review of cultural and power relations in the performing arts of Beksan Trunajaya from the perspective of Pierre Felix Bourdieu's Habitus. (2) to describe the contextual sociological dimensions of cultural and power relations of the Yogyakarta Palace (spiritual, social, and preservation of the natural environment) in the performing arts of Beksan Trunajaya from the perspective of Pierre Felix Bourdieu's Habitus. The type of research used is qualitative research with a semiotic approach dissected with the Roland Barthes semiotic theory approach through the basics of Ferdinand de Sausure's semiotic theory. The study conducted qualitatively dissects the sign system in the Beksan Trunajaya performance by re-reading the visual sign system denotatively and connotatively and exploring the interpretation of values from the visual aspect. The study conducted qualitatively dissects the sign system in the performance of Beksan Trunajaya through the process of reading visual signs, movements, narratives, dialogue, and music. Visual signs include dancer characters, make-up, costumes, behaviour, expressions, and other landmarks surrounding the performance. Visual signs include dancer characters, make-up, costumes, motif forms, and several others surrounding the performance. Signs are born naturally as a reflection of daily life, and several philosophical foundations are put forward substantially in the performance. I was presenting its denotative and connotative meanings in a semi-logical process. The philosophical values that emerge and are found in the relationship between signs in the semiological process consciously or unconsciously reflect the values of moral education. The semiotics of education will be more broadly studied when it is associated with extracting educational values contextual to the sociological conditions and cultural roots that develop in society. The expected results of this research are (1) an explanation of the review of cultural and power relations in the performance art of Beksan Trunajaya from the perspective of Pierre Felix Bourdieu's Habitus. (2) Explanation of the results of the analysis of the contextual sociological dimensions of the cultural and power relations of the Yogyakarta Palace (spiritual, social, and preservation of the Aklam environment) in the performing arts of Beksan Trunajaya in the perspective of Pierre Felix Bourdieu's Habitus